2020
DOI: 10.1007/s11604-020-00975-9
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “COVID-19 infection control protocol inside computed tomography suites”

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In fact, not only it increases the risk of transmission to healthcare workers and other patients, but also the necessary decontamination procedures required after scanning COVID-19 patients could obviously disrupt radiological service availability in a setting where a dedicated COVID-19 CT scanner is not available. Thus, the Fleischner Society Consensus and the American College of Radiology caution towards this approach and the latter suggests the use of CXR to minimize the risk of cross-infection [ 5 , 20 – 22 ]. Keeping all this in consideration, and the fact that CXR is widely available and already routinely obtained in the ED, improving our understanding of the role of COVID-19 CXR radiographic features is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, not only it increases the risk of transmission to healthcare workers and other patients, but also the necessary decontamination procedures required after scanning COVID-19 patients could obviously disrupt radiological service availability in a setting where a dedicated COVID-19 CT scanner is not available. Thus, the Fleischner Society Consensus and the American College of Radiology caution towards this approach and the latter suggests the use of CXR to minimize the risk of cross-infection [ 5 , 20 – 22 ]. Keeping all this in consideration, and the fact that CXR is widely available and already routinely obtained in the ED, improving our understanding of the role of COVID-19 CXR radiographic features is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…22 CT scans have been used as first-line investigation but this has significant challenges in terms of infection control and burden of work on radiology departments. 19 23 CT scan findings typically show a combination of ground glass opacities and peripheral consolidations and are highly sensitive (approaching 97% in some cases, 24 ) although not completely specific. 25 Hence, it has been suggested that CT not be used as a first-line diagnostic test, but is reserved for a patient with high clinical suspicion of COVID-19 and a negative swab result.…”
Section: Role Of Imaging and Lung Ultrasound In Covid-19 Pathwaymentioning
confidence: 99%
“…Radiologists review the CT images far away from the relocatable CT or review CT images online to minimize the number of medical staff entering the relocatable CT. Traditional CT requires a radiographer to position the machine in the scanning room, which inevitably leads to close contact with patients (12,13). The mobile cabin hospital implements paperless communication to reduce unnecessary contact between medical staff and patients.…”
Section: Health Protection Of Medical Staffmentioning
confidence: 99%